Overview of transformative learning II: real-world applications. Issue 6 (1st November 2020) - Anand, Tejwansh S.; Anand, Shohreh V.; Welch, Marguerite; Marsick, Victoria J.; Langer, Arthur
ABSTRACT: This paper provides a description of recent transformative learning applications in four broad areas – health care study abroad, community, and the workplace. The applications were selected from a literature review of English language articles published in peer-reviewed journals from 2010 to 2020. To describe the applications in each of the four broad areas, the paper focuses on the rationale for the studies, their settings, their context, the reported transformation or outcome as well as the impediments and facilitating factors for the transformation. The paper also includes an overview of research designs and instruments that can be generally used to study applications of transformative learning.